Panduan Lapangan Jenis Kupu-kupu di Lingkungan Universitas Lampung Berbasis Android - Aristoteles Aristoteles; Martinus Martinus; Galih Imam Widangga (Universitas Lampung, 2018)
This study aims to design and build a Field-Guide Application of Butterflies’ Species at University of Lampung based on Android. This application is expected to be used as a means of information to determine the classification, family, local name, morphology, butterflies’ food and the benefits of butterflies at University of Lampung. This study uses Waterfall Method and design of Unified Modeling Language (UML), as well as using Black Box Testing to test functional and application. Data in this study consisted of primary data including name of butterfly families, local names, butterfly images (caterpillar, butterfly), descriptions of butterfly species; and secondary data including information about the application, families, local names, butterfly images and descriptions of butterflies (sub-family, genus, species, wingspan, flying speed and food) at University of Lampung. This study uses 5 categories of families and 37 species of butterflies at University of Lampung.The result of the research shows: Equivalence Partitioning Testing result shows that the Application Butterfly of Unila is compatible with all Android OS versions with minimum requirements are 4.0 inch, 4.5 inch, 5.0 inch, 5.5 to 6 inch resolution and based on the classes tested, it indicates that Application Butterfly of Unila works properly.The average of user friendly user ratings obtained is 4.11 included in either category. The average assessment of the interactive variables obtained is 4.08 included in either category. The result of testing data based on user friendly and interactive variable indicates that the application is included in category of Good and tend to Very Good.